Agro-industrial residues in the control of gastrointestinal nematodes of small ruminants and fertilization of forages. - HASSUM, I. C. (2023)
Verminosis in small ruminants can render rural activity impractical, which is still controlled through the administration of anthelmintics. The present study evaluated four agro-industrial residues as fertilizer in the control of GIN of small ruminants in the free-living stage.